Adaptasi Social Media Marketing sebagai Strategi Mempertahankan Eksistensi di Tengah Pandemi Covid-19 - Darmayanti, Luh Putu Eka; Abiyasa, Agus Putu (Jurnal Samudra Ekonomi dan Bisnis, 2022)
This decriptive research uses a qualitative approach that aims to describe the concept of adapting social media marketing as a strategy to maintain existence in the midst of the Covid-19 pandemic, at Umah Sablon Buleleng (USB) Bali as an object. There are seven informants, namely business owners, social media marketing operators, and five consumers of USB Bali. Primary and secondary data as data sources were collected using observation, interview, and documentation techniques. Verification of the validity of the analysis results using data credibility test with source triangulation and technical triangulation. This study obtained three main findings. First, there was a change in consumer behavior experienced by USB Bali consumers before and after the COVID-19 Pandemic, and the New Normal period. Second, the form of digital marketing transformation experienced by USB Bali in the midst of the Covid-19 pandemic. Third, USB Bali has a strategy to maintain its existence in the midst of the Covid-19 pandemic.